Checklist of the amphibians of India, with English common names - Das, I.; Dutta, S. (Centre for Herpetology, Madras Crocodile Bank Trust, 1998)
A checklist of the amphibians of India is presented, along with recommended English common names. The Dubois (1992)scheme of classification is followed for members of the family Ranidae. The fauna at present includes 210 species in nine families.